Characteristics of fluid inclusions in the Alqal Copper-Lead-Zinc deposit, Xinjiang. Issue 1 (February 2021) - Zhang, Chenguang; Tang, Xiangwei; Liu, Kuisong; Zhou, Hongxia; Yuan, Dezhi; Guo, Yueshan; Bao, Junfan; Fan, Jinwei; Zha, Daohan; Yao, Yuan; Ruze, Yusupu; Shi, Xingjun; et al.
Abstract: The Alqal Copper-lead-zinc deposit isl ocated in the Tarim plate of the Xinjiang. It has undergone multiple stages of tectonic mineralization and is an important deposit in the Kuslafu metallogenic belt of the West Kunlun area. Based on the analysis of the metallogenic geological conditions of the deposit, The composition of fluid inclusions in mining area was studied, The characteristics of metallogenic fluid are discussed. The results show that the uniform temperature of gas-liquid two-phase fluid inclusions in the Alqal deposit is between 145°C and 267°C, the average uniform temperature is 191°C; the salinity is 0.71% to 14.87%, and the average salinity is 6.33%. The estimated metallogenic pressure is about 135MPa, and the capture temperature is concentrated around 320°C. The ore-forming fluid has undergone multi-stage superimposed transformation, which is inconsistent with the characteristics of the typical MVT deposit, and it is a sedimentary transformation type deposit.